Perdamaian Sebagai Upaya Penghapusan Proses Pidana (Studi Kasus Putusan Mahkamah Agung Nomor 1600 K/Pid/2009) - Nanang Tomi Sitorus (Universitas Medan Area, 2020)
The reasons in the criminal eradication process are something that often occurs in the criminal law enforcement process, namely the peace of the litigants. Related to the process of eliminating a criminal in the decision of the Supreme Court Number 1600 K / PID / 2009, there is a reason for forgiveness by the victim to revoke his report even though the case is a criminal case. This type of research is normative juridical and analytical descriptive. Legal arrangements related to peace as an effort to eradicate crime are regulated in Article 75 book I chapter III of the Criminal Code and legal considerations by judges related to peace as an effort to eliminate crimes namely that between the Defendant and the victim have a good intention to make peace so that it gives greater benefits and has greater value high, then the form of accountability cannot be asked of the Defendant.